2017
DOI: 10.1007/s10815-017-0962-y
|View full text |Cite
|
Sign up to set email alerts
|

Selection of human blastocysts with a high implantation potential based on timely compaction

Abstract: Of the embryos that formed two cells during the first division within 25.90 h after culture and four cells during the second division within 37.88 h after culture, those that completed compaction within 79.93 h after culture before reaching the blastocyst stage had a high implantation potential.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…This process is conserved in all mammalian species studied so far, but the timing varies. The precise timing of the onset and completion of compaction is important for the successful development of both mouse and human embryos ( Mizobe et al, 2017 ; Kim et al, 2017 ; Skiadas et al, 2006 ). Human embryos in which compaction is either initiated prematurely or delayed have a lower potential to form blastocysts (see Glossary, Box 1 ).…”
Section: Compaction and Polarisation: The First Morphogenetic Transfomentioning
confidence: 99%
“…This process is conserved in all mammalian species studied so far, but the timing varies. The precise timing of the onset and completion of compaction is important for the successful development of both mouse and human embryos ( Mizobe et al, 2017 ; Kim et al, 2017 ; Skiadas et al, 2006 ). Human embryos in which compaction is either initiated prematurely or delayed have a lower potential to form blastocysts (see Glossary, Box 1 ).…”
Section: Compaction and Polarisation: The First Morphogenetic Transfomentioning
confidence: 99%
“…However, the determination of embryonic development 72 h after insemination might be more appropriate for the "compacting morula" rather than the "morula" in mice. Although previous studies have observed compaction and subsequent embryonic development using time-lapse technology in human embryos, these focused on vacuolization in blastomeres [24], timing of morula formation [22,23,25,26], and patterns of compaction with or without extruded blastomeres [22,27]. There have been, to our knowledge, no previous studies involving the observation of a temporary loosening of compaction during the formation of morula beginning with the initiation of compaction in human embryos [44].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the automatic capture of time-lapse images would provide useful information for embryo selection for subsequent embryo transfer. Previous studies have investigated pronuclear formation [15,16], timing of cleavage [16,17], fragmentation [18][19][20][21], compaction [22][23][24][25][26][27], blastocoel formation [26,28], and the shape of the inner cell mass [29] in human zygotes/embryos using a time-lapse monitoring system. Embryos that cleave early at the first cleavage have a higher potential for subsequent pre-and post-implantation development [17,[30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…The accumulation of PARD6B also seems to occur about 90 h post fertilization [114]. The human embryo then consists of at least 16 cells and compaction has completed [10,12,103]. This is later than in the mouse, which compacts and polarises during the 8-cell stage [11,20].…”
Section: Internalisation Of the Icm Precursorsmentioning
confidence: 99%
“…While a minority of embryo start compaction as early as during the 8-cell stage, the majority of human embryos begin compaction during the 4 th wave of cleavages, with at least 9 blastomeres and most finish compaction during the 16-cell stage [10]. Embryos compacting less than 80 h after fertilization show higher rate of implantation and live birth than embryos compacting after the 80 h mark [12,101,103]. What controls the timing of compaction remains unclear though.…”
Section: Compactionmentioning
confidence: 99%